Paradise fish (Macropodus opercularis) as a complementary translational model for emotional and cognitive function - Zoltán K. Varga; Diána Pejtsik; Tímea Csorvási; Éva Mikics; Ádám Miklósi; Máté Varga (Communications Biology)
Abstract Zebrafish have revolutionised physiological screening in vertebrates, however, their strong sociality present challenges for interpreting behavioural assays conducted on individual subjects. To retain the advantages of the zebrafish model while addressing its limitations, we propose the use of a solitary species—the paradise fish—as a complementary model system. We compared paradise fish and zebrafish of late larval stage in social and non-social exploratory tasks, anxiety tests and in a working memory assay to assess their performance in these individual-based challenges. We found that in contrast to zebrafish, paradise fish did not show social approach in sociability tests, their exploratory behaviour was unaffected by the presence of a conspecific, and social isolation did not impair their performance during anxiety tests. Intra- and intertest variability measures of different anxiety tests revealed that, compared to zebrafish, paradise fish express more consistent, repeatable patterns of exploratory and risk-avoidance behaviour across time and contexts. We also showed that paradise fish exploration of the Y-maze is dominated by arm alternations, suggesting advanced working memory. Considering the results of this systematic comparison and the natural history of the two species we recommend prioritizing zebrafish in social tasks, while favouring paradise fish in individual-based behavioural assays.